2011
DOI: 10.1093/jb/mvr063
|View full text |Cite
|
Sign up to set email alerts
|

A cell-based assay to screen stimulators of the Hippo pathway reveals the inhibitory effect of dobutamine on the YAP-dependent gene transcription

Abstract: The mammalian Hippo pathway is composed of mammalian Ste20-like (MST) kinases and large tumour suppressor (LATS) kinases. Upon the activation of the pathway, MST kinases phosphorylate and activate LATS kinases, which in turn phosphorylate transcriptional co-activators, yes-associated protein (YAP) and transcriptional co-activator with PDZ-binding motif (TAZ), recruit them to the cytosol from the nucleus and turn off cell cycle-promoting and anti-apoptotic gene transcriptions. Thus, the pathway restricts cell o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
118
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 20 publications
2
118
0
Order By: Relevance
“…In the latter scenario, glucagon, epinephrine, and a dopamine receptor agonist induce YAP/TAZ phosphorylation. Interestingly, in a screen for YAP inhibitors, dobutamine has been shown to inhibit YAP (Bao et al 2011). Dobutamine is an agonist for the b1 adrenergic receptor, which likely inhibits YAP by activating Ga s .…”
Section: G-protein-coupled Receptor (Gpcr) Signaling: Sensing Diffusimentioning
confidence: 99%
“…In the latter scenario, glucagon, epinephrine, and a dopamine receptor agonist induce YAP/TAZ phosphorylation. Interestingly, in a screen for YAP inhibitors, dobutamine has been shown to inhibit YAP (Bao et al 2011). Dobutamine is an agonist for the b1 adrenergic receptor, which likely inhibits YAP by activating Ga s .…”
Section: G-protein-coupled Receptor (Gpcr) Signaling: Sensing Diffusimentioning
confidence: 99%
“…The rat anti-YAP monoclonal antibody used was described previously (43). The following antibodies and reagents were obtained from commercial sources.…”
mentioning
confidence: 99%
“…The TEAD reporter assay was performed with HEK293 cells as described previously (43). C2C12 cells were plated at 1 ϫ 10 5 /well in 12-well plates and cultured overnight.…”
mentioning
confidence: 99%
“…However, the role of the classical Hippo cascade and its downstream effectors YAP and TAZ remained unclear in this study. H 2 O 2 -induced activation of the canonical Hippo cascade could promote phosphorylation and nuclear localization of the downstream effectors, which has been demonstrated recently for YAP (37). This inactivation of YAP would promote cell death, and consistently it has been shown that both decreased Lats1 activity (31) as well as increased YAP activity could protect cardiomyocytes against H 2 O 2 -induced cell death (38).…”
Section: Discussionmentioning
confidence: 77%